A COMPARATIVE STUDY OF MALES AND FEMALES BUYING BEHAVIOR TOWARD MUSIC PLAYING IN STORE IN MANADO - Manoppo, Eukaristi (Jurnal Berkala Ilmiah Efisiensi, 2016)
Music is a crucial element of everyday life. The music has influenced many people, including gender and group of age. While within marketing, it has been demonstrated that music influences the shopping experience in store atmospherics and can affect the consumers. This research aims to find out the influence of music playing in store on the buying behavior which will be compared between males and females buying behavior. 100 customers of Planet Surf Mantos were surveyed as samples by using purposive sampling technique and sample size. This study used simple regression analysis and independent sample ttest method with results that music playing in store has significantly influence buying behavior and there’s significant difference between males and females buying behavior. Music makes consumers spend more time in the store and will lead to more profit for the marketers.